2009
DOI: 10.1086/600108
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Monoclonal Antibody Treatment Targeting Respiratory Syncytial Virus (RSV) G Protein Mediates Viral Clearance and Reduces the Pathogenesis of RSV Infection in BALB/c Mice

Abstract: Because the G protein of respiratory syncytial virus (RSV) has a CX3C chemokine motif that has been associated with the ability of RSV G protein to modulate the virus-induced host immune response, we examined whether therapeutic treatment with an anti-RSV G monoclonal antibody (mAb), 131-2G, that blocks the CX3C-associated activity of RSV G protein might decrease the pulmonary inflammation associated with infection in BALB/c mice. The results show that treatment with mAb 131-2G on day 3 after RSV infection red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
129
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(137 citation statements)
references
References 32 publications
8
129
0
Order By: Relevance
“…However, in a different study by the same group using RSV A2 and BALB/c mice, instillation of a neutralizing monoclonal antibody against the G protein of RSV on day 5 p.i. actually doubled pulmonary neutrophil accumulation when the mice were examined 2 days later on day 7 (14). This observation resembles our finding of increased neutrophil accumulation in the lungs of RSV line 19-infected newborn CX3CR1 -/-mice on day 7 p.i.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…However, in a different study by the same group using RSV A2 and BALB/c mice, instillation of a neutralizing monoclonal antibody against the G protein of RSV on day 5 p.i. actually doubled pulmonary neutrophil accumulation when the mice were examined 2 days later on day 7 (14). This observation resembles our finding of increased neutrophil accumulation in the lungs of RSV line 19-infected newborn CX3CR1 -/-mice on day 7 p.i.…”
Section: Discussionsupporting
confidence: 87%
“…also suggested to enhance viral fusogenic activity. Studies using antibodies targeted against the G protein have shown an ability to modulate immune response against virus infection (13,14). The G glycoprotein can interact with the chemokine receptor CX3CR1 due to the presence of the CX3C motif in its amino acid sequence (15).…”
Section: Introductionmentioning
confidence: 99%
“…Support for potential therapeutic utility of targeting the G protein central conserved cysteine-noose region has recently been provided by direct comparison of murine monoclonal anti-F and anti-G Abs with low nanomolar affinities in a mouse treatment model (31), with superior performance demonstrated by the anti-G Ab for reducing both viral load and markers of airway inflammation. The results presented here further support the utility of an anti-G Ab in reducing viral load in both prophylactic and postinfection treatment mouse models.…”
Section: Discussionmentioning
confidence: 99%
“…Murine Abs to the central conserved region of the G protein have shown efficacy in prophylactic mouse (29) and cotton rat models (30). A recent report showed that such a murine mAb delivered postinfection decreased both viral replication and the associated pulmonary inflammatory response (31). Furthermore, the antiviral and immunomodulatory features of the mAb were shown to be separable functions by comparing the full IgG to an F(abЈ) 2 fragment (32).…”
mentioning
confidence: 99%
“…Monoclonal antibodies (mAbs) are an important class of biomolecules that are used in the treatment of various diseases such as cancer, multiple sclerosis, rheumatoid arthritis, lupus, and respiratory diseases (Choy et al, 1998; Cobleigh et al, 1999; Haynes et al, 2009; Helliwell and Coles, 2009; Robak and Robak, 2009). During mAb process development, aggregates and fragments have to be removed to adequate levels due to their associated risks with increased immunogenicity and potential effects on drug efficacy (Fan et al, 2012; Rosenberg, 2006).…”
Section: Introductionmentioning
confidence: 99%